Validation of Sensory Processing Sensitivity Scale for a Sample of University Students in Iraq - Mahfouz, Dr. Souhair A (International Journal of Psychosocial Rehabilitation, 2020)
The current study attempted to examine the structure and psychometric properties of the measurement of Sensory-Processing Sensitivity (SPS) for a sample of university students in Iraq. The study questions addressed were: What is the structure of (SPS) measurement for university students in Iraq? Is (SPS) measurement has appropriate psychometric properties? A total of 165 students from University of Baghdad completed the (SPS), including males (N=89) and females (N=76). The student’s ages ranged from (18 to 22) with an average age (20.7) and SD (2.1). Confirmatory factor analysis (CFA) was used. The results indicated that the (SPS) has multidimensional structure which includes: Ease of excitation, Low sensory threshold, and aesthetic sensitivity. Also, the scale has appropriate psychometric properties.